Small colony variant of Escherichia coli isolated from a recurrent urinary tract infection- a case report - Dutt, Shivendra; N, Nagalakshmi; K.L, Shobha (International Journal of Health, 2014)
Introduction: Small colony variant of Escherichia coli may cause persistent and recurrent infections in human. These slow growing phenotypic variants are difficult to identify and mislead the diagnosis which can lead to choice of inappropriate antibiotics. In this case report we are presenting a case of recurrent urinary tract infection which was associated with small colony variants of E. coli.Case presentation: A two year old male child was admitted to the hospital with a complaint of passing thin stream of urine. One month earlier the child had been previously diagnosed with bilateral grade five Vesicoureteral reflux. Child had developed recurrent urinary tract infection caused by small colony variants of E. coli.Conclusion: child had undergone bilateral ureter reimplantation as part of treatment to Vesicoureteral reflux. Since vesicoureteral reflex condition is one of the risk factor to develop urinary tract infections. Repeated exposure to antibiotic might have been induced stress condition to bacteria and emerged as slow growing sub population of E. coli.